Binary mixtures of imidacloprid and thiamethoxam do not appear to cause additive toxicity in fathead minnow larvae (Pimephales promelas) - Jeninga, Anya J.; Kooij, Nicole; Harrahy, Elisabeth; King-Heiden, Tisha C. (Frontiers in Toxicology, 2023)
Introduction: Considerable use of neonicotinoid insecticides has resulted in their detection in surface waters globally, with imidacloprid (IM) and thiamethoxam (TM) frequently found together. Neonicotinoids are selective agonists for invertebrate nicotinic acetylcholine receptors (nAChR) leading to paralysis and death. While not overtly toxic to vertebrates, growing evidence suggests that chronic exposure to individual neonicotinoids can cause adverse health effects in fish. This work examined whether chronic exposure to binary mixtures of imidacloprid (IM) and thiamethoxam (TM) would be more toxic to fathead minnow (Pimephales promelas) larvae than either insecticide alone. Materials and Methods: Embryos were exposed to a 1:1 mixture of IM and TM (0.2, 2, 20, 200 or 2000 µg/L of each pesticide) or a 1:5, 1:10, or 1:20 mixture of IM and TM (0.02 µg/L of IM with 0.1, 0.2, or 0.4 µg/L of TM) for a total of eight days. Survival, developmental toxicity, embryonic motor activity, and startle escape responses were quantified. Results: Survival and growth were reduced, and hatching induced by exposure to a 1:1 mixture containing > 2 µg/L of each insecticide, but not following exposure to mixtures containing environmentally-relevant concentrations. Acute exposure to a 1:1 mixture did not alter embryonic motor activity; however, chronic exposure to these mixtures resulted in a slight but significant decrease in embryonic movements. Only 1:1 mixtures of high concentrations of IM and TM altered the startle escape response by increasing latency of response; however, a significant proportion of fish exposed to 1:1 mixtures had altered latency and burst speed. Taken together, these behavioral indicators of nAChR activation suggest that in mixtures, neonicotinoids could interfere with nAChR signaling despite their low affinity for the nAChR. Conclusion: Our findings suggest that toxicity of binary mixtures of IM and TM is primarily driven by IM, and that mixtures of IM with TM do not appear to cause significant additive toxicity when compared with our previous studies evaluating each neonicotinoid alone. Given the limited toxicological data available for mixtures of neonicotinoid insecticides in fish, further study is required to better understand the ecological risks these insecticides may pose to aquatic ecosystems.